The Accumulation of Tau-Immunoreactive Hippocampal Granules and Corpora Amylacea Implicates Reactive Glia in Tau Pathogenesis during Aging - Connor M. Wander; Jui-Heng Tseng; Sheng Song; Heba A. Al Housseiny; Dalton S. Tart; Aditi Ajit; Yen-Yu Ian Shih; Rebecca Lobrovich; Juan Song; Rick B. Meeker; David J. Irwin; Todd J. Cohen (iScience, 2020)
Summary: The microtubule-associated tau protein forms pathological inclusions that accumulate in an age-dependent manner in tauopathies including Alzheimer's disease (AD). Since age is the major risk factor for AD, we examined endogenous tau species that evolve during aging in physiological and diseased conditions. In aged mouse brain, we found tau-immunoreactive clusters embedded within structures that are reminiscent of periodic acid-Schiff (PAS) granules. We showed that PAS granules harbor distinct tau species that are more prominent in 3xTg-AD mice. Epitope profiling revealed hypo-phosphorylated rather than hyper-phosphorylated tau commonly observed in tauopathies. High-resolution imaging and 3D reconstruction suggest a link between tau clusters, reactive astrocytes, and microglia, indicating that early tau accumulation may promote neuroinflammation during aging. Using postmortem human brain, we identified tau as a component of corpora amylacea (CA), age-related structures that are functionally analogous to PAS granules. Overall, our study supports neuroimmune dysfunction as a precipitating event in tau pathogenesis.